Association between TP53 and p21 genetic polymorphisms and acute side effects of radiotherapy in breast cancer patients - Tan, Xiang-Lin; Popanda, Odilia; Ambrosone, Christine B.; Kropp, Silke; Helmbold, Irmgard; Fournier, Dietrich von; Haase, Wulf; Sautter-Bihl, Marie Luise; Wenz, Frederik; Schmezer, Peter; Chang-Claude, Jenny (Breast cancer research and treatment, 2006)
p53 and p21 play an important role in G1/S checkpoint control in response to ionizing radiation. Yet the genetic polymorphisms in these genes have not been investigated with respect to radiation toxicity in patients. We therefore assessed the association between TP53 Arg72Pro, p53PIN3 and p21 Ser31Arg polymorphisms and the risk of acute skin toxicity after radiotherapy in a prospective study of 446 female breast cancer patients (average age 60.3 +/- 9.0 years) receiving radiotherapy after breast conserving surgery. The p53PIN3 polymorphism was determined by standard PCR, and TP53 Arg72Pro and p21 Ser31Arg polymorphisms using melting point analysis of sequence-specific hybridization probes. The development of acute skin toxicity (moist desquamation) was modelled using Cox proportional hazards, accounting for cumulative biologically effective radiation dose. Overall, the development of acute skin toxicity, which presented in 77 patients, was not significantly associated with the polymorphisms studied. Risks were however differential by body mass index. Compared to non-carriers, TP53 72Pro carriers had a non-significantly decreased risk of acute skin toxicity in normal weight women (hazard ratio 0.46, 95% CI, 0.18-1.18) but not in overweight patients (hazard ratio 1.07, 95% CI, 0.61-1.89) (p(interaction) =0.14). Haplotype analysis for the TP53 polymorphisms suggested that effect modification by TP53 72Pro may differ according to the p53PIN3 allele (p(interaction)=0.06). Furthermore, in TP53 72Pro carriers with p21 Ser/Ser genotype, the occurrence of acute toxicity was reduced in normal weight but not overweight patients. In conclusion, the TP53 72Pro variant may be associated with the development of acute skin toxicity after radiotherapy in patients with normal weight. Large clinical studies are needed to clearly confirm this association.